Psychological stress in students of a peruvian public university during the first wave of COVID-19 - Poma-Tovar, Mara Romyna (2022)
Introduction. The COVID-19 pandemic, the lockdown, and suspension of activities were important psychological stressors. University students are a vulnerable population for high stress levels. Objective. To determine the levels of psychological stress and identify associated factors in the student population of a peruvian public university. Methods. Cross-sectional observational study. We applied an online survey on characteristics related to university studies and the 13-item Global Perception of Stress Scale (PSS-13). The questionnaire was applied in the framework of the first wave of the COVID-19 pandemic. High stress was considered to be those students with a score above the 75th percentile. We compared the mean scores of the PSS-13 according some students characteristics with the Student’s t-test or the Mann-Whitney U-test. In addition, multivariate analyses was performed to recognize factors related to high stress. Results. 2647 university students participated in this study. 1566 (59.2%) were female. The age of the students was 21 years (IQR: 19 – 23). The stress score was 27.6 ± 7.1. The variables related to high level of stress were female sex, university academic year, having pending courses, chronic illness, and worrying about the future. Conclusions. During the first wave of COVID-19, university students presented high levels of stress. Being a woman, the academic year, having pending courses, chronic illness and worrying about the future are risk factors for presenting a high level of stress in a state university in Peru.